Changing diameters of cerebral vessels with age in human autopsy specimens: Possible relationships to atherosclerotic changes - ÖZDOĞMUŞ, NECMETTİN ÖMER (GEORG THIEME VERLAG KG, 2008)
Aims/Objectives: It has been previously recognized that the anatomy of arterial bifurcations influences blood flow and has a significant role in the development of vascular disease. Material and Methods: In the present study, we measured the average diameters of the infernal carotid (ICA), anterior cerebral (ACA), and middle cerebral arteries (MCA) in autopsy cases. We also calculated the outflow to inflow area ratios for four distinct age groups and for each gender, using 33 adult autopsies and 7 fetuses. Results: The area ratios decreased with age in both male and female samples. The decrease in the male (30 %, p < 0.05) was greater than the decrease for the female (17 %, p > 0.05). The average diameter of the ACA, MCA and ICA of both female and male cases increased up to the 25-44 age group, decreased for the 45-64 age group, with a second increase above the age of 65. Conclusions: The decrease in the area ratios and the pattern of changes of the dimensions of the cerebral vessels with age are useful to examine the causal relationships of these pathologic conditions and raises novel questions about age and gender differences in the structure of the intracranial vessels.
Keywords: intracranial arteries; arterial bifurcations; blood flow; gender differences; area ratio; CAROTID BIFURCATION ANATOMY; POSTMENOPAUSAL WOMEN; SIDE DIFFERENCES; ARTERIES; PLAQUE; SEX; LOCALIZATION; DISEASE; RISK; APEX